2007
DOI: 10.1029/2006tc002035
|View full text |Cite
|
Sign up to set email alerts
|

Model of successive granite sheet emplacement in transtensional setting: Integrated microstructural and anisotropy of magnetic susceptibility study

Abstract: [1] This study presents a model of successive emplacement of three granite plutons in transtensional deformation regime controlled by the preextensional synconvergent history of the lower and middle crust in the central Vosges Mountains (France). The complex compressional orogenic structure recorded a vertical exhumation-related fabric in midcrustal levels which was overprinted by the regional extension. Three successively emplaced granite sheets exploited the inherited vertical anisotropy obliquely oriented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 74 publications
(114 reference statements)
2
25
0
Order By: Relevance
“…We show that the variations of fabric symmetries and degrees of AMS anisotropy may result from complex deformation overprints. Such a possibility was already supported by independent structural studies (Kratinová et al 2007(Kratinová et al , 2010Parry et al 1997;Schulmann et al 2009). …”
Section: Numerical Modeling Of Magnetic Fabricmentioning
confidence: 85%
See 2 more Smart Citations
“…We show that the variations of fabric symmetries and degrees of AMS anisotropy may result from complex deformation overprints. Such a possibility was already supported by independent structural studies (Kratinová et al 2007(Kratinová et al , 2010Parry et al 1997;Schulmann et al 2009). …”
Section: Numerical Modeling Of Magnetic Fabricmentioning
confidence: 85%
“…Several modern structural studies show that granitoids often exhibit multiple foliations (Ž ák et al 2007, 2008), but the associated variations in AMS fabrics were never discussed. Kratinová et al (2007), Schulmann et al (2009) and Kratinová et al (2010) combined both structural and AMS fabric studies to unravel polyphase deformation of migmatitic terrains and intrusions of granite sheets. These studies showed the presence of multiple fabrics and development of prolate shapes of AMS ellipsoids in areas of fabric transpositions developed at a high angle between two planar fabrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…335 Ma in the northern Vosges (Altherr et al 2000) most likely reflects the magmatic arc related to this event. The age of arc magmatism coincides with a major extension associated with partial melting and emplacement of sheeted intrusions in the southern highgrade core zone of the Vosges (Rey et al 1992;Kratinová et al 2007;Schulmann et al 2009). It is therefore the central part of the Vosges Mountains that probably recorded the extensional and high temperature event associated with the southward subduction of the Rhenohercyian basin.…”
Section: Origin Of the Southern Vosges Basinmentioning
confidence: 97%
“…Although well documented (Burg et al 1994;Faure 1995), the Stephanian-Permian NE-SW stretching must be distinguished from the NW-SE Namurian-Westphalian extension reported from the western part of the Massif Central (Faure 1995 Laurussia has resulted in thrust tectonics and metamorphism in the Vosges Mountains (Fluck et al 1987;Rey et al 1989;Schulmann et al 2002), and in the Black Forest Eisbacher et al 1988;Echtler and Chauvet 1992). The thickened crust experienced synorogenic to postorogenic extension represented by detachment faults and syntectonic plutons, documented in the Vosges Mountains (Rey et al 1992;Kratinova et al 2007), and in the Black Forest (Krohe and Eisbacher 1988;Eisbacher et al 1988;Echtler and Chauvet 1992).…”
Section: Regional Correlations Of the Autun And La Serre Faultsmentioning
confidence: 96%